Histopathological analysis of placental lesions caused by Chlamydia abortus 1B vaccine strain in vaccinated ewes - Caspe, Sergio Gaston; Livingstone, Morag; Wattegedera, Sean Ranjan; Aitchison, Kevin; Underwood, Clare; Milne, Elspeth; Sargison, Neil Donald; Chianini, Francesca; Palarea-Albaladejo, Javier; Longbottom, David (Microbiology Society, 2024)
Poster. Publicado además en: Access Microbiology, 4 (5) (2022)